The legal status of the states in Malaysia before independence: Whether we had been colonized? - Mokhtar, Khairil Azmin (2012)
This paper seeks to clarify the legal status of the states in Malaysia before the Independence in 1957 as well as the status of Sabah and Sarawak before they joined Malaysia in 1963. There has been a controversy quite recently regarding the status of the states before 31st of August 1957. This issue relates to the question whether the states in Malaysia had been colonised or not. There is a view that the country has never been colonized because the British was invited to give advice the Malay Rulers of the peninsula as a result of protection agreements signed between the Sultans and the British’s representatives. These agreements did not allow the British to exercise any jurisdiction which means the states had never been under British colonization. On the other hand there are people who argue that the Independence terminated British rule over the country which means the state had been colonized by the British. The paper attempts to unravel the legal side of the issue so that the question of colonization of the states would be understood better.